A Revolt Against The Christian Concept Of Woman In Nathaniel Hawthorne's The Scarlet Letter : A Feminist Approach - Sulistiyani, Endang Nuning (2003)
This thesis is primarily intended to identify how the revolt of the major character against the Christian concept of woman is reflected in Nathaniel Hawthorne's The Scarlet Letter. It is a qualitative study. The data are collected by using two kinds of technique: documentation and library research. The technique of data analysis is descriptive analysis. The research significance is to give contribution to the body of knowledge, particularly the literary study on Nathaniel Hawthorne's The Scarlet Letter. The result of analysis confirms that Hester Prynne tries to fight against the Christian concept of woman by rejecting the type of woman on position, role, rights and participation which are characterized by the concept of woman on Christian belief. At last it is known that Hester Prynne's fight against the Christian concept of woman can be categorized as feminist attitude.